Tradutological Behavior, Feminisms and Literature for Children and Young Adults: some Examples from the Galician Sphere - Pena Presas, Montse (Madrygal. Revista de Estudios Gallegos, 2020)
This article discusses Galician Literature for Children and Young Adults from the traces that feminism and translations left in it. A series of periods regarding the impact of feminism on books for children and young adults were established in an attempt to study whether feminist texts from other literary systems preceded and served as models within the Galician frame of literature for children and young adults; whether authors committed to feminism in Galicia were also translators of coeducational texts; and whether at present the Galician literary field has reference works in approaching issues such as alternative masculitines, sexual identities or *trans-characters. By analysing particular cases, it will be confirmed, first, that Galician literature took time to import feminist works for young readers; second, that Galician works were innovative with regard to feminism –although some of them reflect the influence of certain models–; and, third, that in times when translations were needed due to the access of Galician language to Teaching, texts from nearby traditions or from Children's classic literature were privileged. In addition, stress will be on the fact that, recently, translation of women authors is becoming more and more frequent at the same time that we can count on several interesting feminist texts. However, this is happening without any prior planning which may guarantee the quality and the mechanisms for cultural diversity that a literary system with the particularities of the Galician one would need.
Keywords: Translation; Feminism; Children’s and Young Literature; Galician Literary System